The oncocyte that went places: Diagnosis with EUS‐guided FNA. Issue 11 (26th September 2011) - Safdar Khan, Ali; Crowe, David R.; Eloubeidi, Mohamad A.
<x xml:space="preserve">Abstract</x> Although uncommon, Hurthle cell neoplasms have a characteristic histologic and cytologic features which often aid in the diagnosis of these lesions. In fine needle aspiration biopsies, determining malignant potential on cytologic features is challenging unless other evidence of malignancy (such as metastases) are known. The role of EUS‐guided FNA in diagnosing superior mediastinal masses has been described previously. It's role in evaluating subcarinal metastases from lung cancer primaries have also heen studied. However we describe metastatic thyroid Hurthle cell carcinoma to the subcarina diagnosed through EUS‐guided FNA combining the unique cytologic features o Hurthle cell neoplasms and the versatility ofthe endoscopic ultrasound to reach a diagnosis in this unusual neoplasm. Diagn. Cytopathol. 2013;41:977–979. © 2011 Wiley Periodicals, Inc.